2016
DOI: 10.1007/s12649-016-9515-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomethanation Potential of Wetland Biomass in Codigestion with Pig Slurry

Abstract: Check the metadata sheet to make sure that the header information, especially author names and the corresponding affiliations are correctly shown.• Check the questions that may have arisen during copy editing and insert your answers/ corrections.• Check that the text is complete and that all figures, tables and their legends are included. Also check the accuracy of special characters, equations, and electronic supplementary material if applicable. If necessary refer to the Edited manuscript.• The publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…This result should not be surprising because as the DORG increases, the amount of lignin present in the plant tissue increases (Table 4). It is known, indeed, that AD is negatively affected by the lignin content (Marchetti et al, 2016). Moreover, the cuts with lower DORG are characterized by an average C/N of 27 (Table 5) which fell within the range considered optimal for AD (20–30; Hagos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This result should not be surprising because as the DORG increases, the amount of lignin present in the plant tissue increases (Table 4). It is known, indeed, that AD is negatively affected by the lignin content (Marchetti et al, 2016). Moreover, the cuts with lower DORG are characterized by an average C/N of 27 (Table 5) which fell within the range considered optimal for AD (20–30; Hagos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The BMP from each agro-waste (table 3) is pretty comparable to BMP values of cultures used for energy production in other studies reported at similar conditions and inoculum (Chandra et al, 2012;Corro et al, 2014;Darwin et al, 2014;Kaur et al, 2020;Mustafa et al, 2018;Noonari et al, 2019;Nosratpour et al, 2018;Nurk et al, 2017;Pazmiño-Hernandez et al, 2019;Petersson et al, 2007;Sajad Hashemi et al, 2019;Villa Gomez et al, 2019). Other authors achieved similar values using other inoculum sources (Guerini Filho et al, 2019;Marchetti et al, 2016;Nzila et al, 2010). They also point out the need to pre-treat such biomass to increase biodegradability and biogas yield by scaling up the technology.…”
Section: Source: Elaborated By the Authorsmentioning
confidence: 56%
“…The methane yield was twofold higher than the total amount of straw without pretreatment and huge effect on digestibility of pretreated by fungi biomass has a microbial consortia in the process (Zhong et al, 2011). In the next study of biogas production (Vasmara et al, 2015; Marchetti, Vasmara & Florio, 2016), lignolytic white-rot fungi and cellulolytic or xylanolytic fungi were compared regarding biogas production. Pretreated wheat straw with or without pig slurry during the co-digestion process was used as a substrate.…”
Section: Resultsmentioning
confidence: 99%